KONSEP PENDIDIKAN ANAK PADA KISAH NABI IBRAHIM DAN LUKMAN AL-HAKIM DALAM AL-QUR’AN - ahmad muhajir; Munirul Abidin; Aunur Rofiq (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2022)
Education according to Islam is an effort so that people recognize and acknowledge God's place in this life. As educators, the main thing as parents is to prepare their children to be pious and pious children because the education they get will be their survival in the future as Prophet Ibrahim educated his children because he knew how important science was. And as Lukman al-Hakim educates his children with advice and gentle words (wisdom). Meanwhile, the focus of the research discussed in this study are: (1) What educational values ??are contained in the story of Prophet Ibrahim and Lukman al-Hakim? (2) What is the strategy for instilling these values? (3) What are the implications for the development of education in Indonesia? To achieve this goal, the researcher uses a research method with a philosophical approach. This type of research is library research, namely research whose main object is books or other library sources. That is, data is sought and found through a literature review of books or other sources relevant to the discussion. The results of this study are: (1) The concept of Children's Education in the Story of the Prophet Ibrahim, namely: a. Rational (When Seeking God), b. Tawhid/Belief (Seeing a bird that is turned on), c. Istiqomah (When it is about to be burned), d. Dare to Speak the Truth (Against King Namrud), e. Patient and Not Desperate, (Asking for Descendants), f. Words and Sincerity (Slaughtering Ismail). (2) The concept of children's education in the story of Lukman al-Hakim, namely: a. Prohibition of Associating Associates with Allah, b. Glorifying Parents and Gratitude, c. Be Careful in Acting Because Every Action Gets a Reply, d. Establishing a Sholet (Amar Ma'ruf Nahi Mungkar), e. Can't Be Arrogant (3) The education of children in the story of Prophet Ibrahim and Lukman al-Hakim where the education given to their children is very good at instilling educational values ??to their children and the priority is education about the religion of monotheism, morals